Modeling riparian vegetation responses to flow alteration by dams and climate change - Auerbach, Daniel Albert, author; Poff, N. LeRoy, advisor; Bledsoe, Brian, committee member; Boone, Randall, committee member; Merritt, David, committee member; Webb, Colleen, committee member (Colorado State University. Libraries, 2013)
As the interface between freshwater and terrestrial ecosystems, riparian vegetation is a critical influence on biodiversity maintenance and ecosystem service production along river corridors. Understanding how altered environmental drivers will affect this vegetation is therefore central to sound watershed management. A river's flow regime exerts a primary control on the type and abundance of riparian vegetation, as differing adaptations to changing discharge levels mediate plant recruitment and persistence. Models of the relationships between flow and vegetation, generalized across species in terms of flow response traits such as flood tolerance, provide a means to explore the consequences of hydrologic alteration resulting from dams and climate change. I addressed these issues through development of a stage-structured model of woody riparian vegetation driven by variation in annual high flows. Simulation experiments offered insight into the potential trajectories of competing vegetation trait types relative to scenarios of dam construction, re-operation and removal. Modifying the size and frequency of the floods responsible for both disturbance mortality and establishment opportunities altered the relative abundance of pioneer and upland cover. Yet, qualitative differences in simulated outcomes resulted from alternative assumptions regarding seed limitation and floodplain stabilization, illustrating the need to carefully consider how these factors may shape estimated and actual vegetation responses to river regulation. In addition, I linked this simulation approach with an integrated watershed-modeling framework to assess the relative risk of invasion by the introduced plant Tamarix under multiple climate change scenarios. Though warming may increase the potential for Tamarix range expansion by weakening thermal constraints, the results of this work supported the expectation that hydrogeomorphic variation will control how this potential is realized. With simulated invasion risk strongly dependent on shifts in both the magnitude and timing of high flows, model outcomes underscored the importance of accounting for multiple, interacting flow regime attributes when evaluating the spread of introduced species in river networks. This research suggested the utility of simplified but process-based simulations of riparian flow-ecology relationships, demonstrating that such models can establish a first approximation of the potential consequences of management decisions and can highlight key questions for additional research, particularly where data are scarce and uncertainty is high.
Keywords: dams; riparian vegetation; flow-response traits; Tamarix